Patients With Ankylosing Spondylitis Are Associated With High Risk of Fibromyalgia: A Nationwide Population-Based Cohort Study - Gau, Shuo-Yan; Lee, Yung-Heng; Tsou, Hsi-Kai; Huang, Jing-Yang; Chen, Xinpeng; Ye, Zhizhong; Wei, James Cheng-Chung (Frontiers in Medicine, 2021)
Abstract Objectives The main purpose of this retrospective cohort study was to provide evaluation of Ankylosing spondylitis (AS) patients’ fibromyalgia risk in different age and sex subgroups through analyzing large study samples. Methods Datasets from the National Taiwan Insurance Research Database (NHIRD) were retrieved in this retrospective cohort study. This study was approved by the Institutional Review Board of Chung Shan Medical University (IRB permit number CS15134). Within Longitudinal Health Insurance Database (LHID), the subset of NHIRD, we identified AS patient to observe the risk of further fibromyalgia. The exposure cohort included patient with newly-diagnosed AS (ICD-9-CM:720.0) during 2000-2013. After 1:4 age-sex matching and 1:2 propensity score matching adjusting potential confounders, individuals without AS were identified as comparison cohort. Adjusted hazard ratio of subsequent development of fibromyalgia in people with AS were evaluated. Further stratification analyses of different age and gender were done to validate the results. Results In total, 17 088 individuals were included in the present study, including 5 696 patients with AS and 11 392 individuals without AS. Respective incidence rates (per 1 000 person-months) of fibromyalgia was 0.52 (95% C.I., 0.46-0.59) in AS cohort and 0.39 (95% C.I., 0.35-0.44) in non-AS cohort. Comparing with non-AS cohort, aHR of developing fibromyalgia was 1.32 (95% C.I., 1.12-1.55) in people with AS. This association was consistent in both statistical models of 1:4 age-sex matching and 1:2 propensity score matching. Conclusion Patients with AS were associated with higher risk of fibromyalgia, especially in those over 65 years old. In managing patients with AS, clinicians should be aware of this association on impact on diagnosis, disease activity evaluation and treatment. Key words: ankylosing spondylitis, fibromyalgia, cohort, population-based study, NHIRD